High neutrophil‐to‐lymphocyte ratio is a predictor of short‐term survival for patients with recurrent cervical cancer after radiation‐based therapy. Issue 5 (21st February 2021) - Taguchi, Ayumi; Nakajima, Yujiro; Furusawa, Akiko; Yoshino, Yasunori; Takao, Maki; Kashiyama, Tomoko; Kino, Nao; Yasugi, Toshiharu
Abstract: Aim: Patients with recurrent cervical cancer after radiotherapy have poor prognoses because of the lack of effective treatment options. Biomarkers to predict survival outcomes for recurrent cervical cancer are warranted because patients with limited life expectancy sometimes benefit from less aggressive treatment in combination with early palliative care. Therefore, we aimed to explore a predictive biomarker for the outcomes of patients with recurrent cervical cancer. Methods: We retrospectively investigated 231 patients initially treated with radiation‐based therapy between January 2004 and December 2015. The associations between clinicopathological features at the time of relapse and overall survival after relapse were assessed. As factors which reflect patients' conditions, we particularly focused on C‐reactive protein‐to‐albumin ratio (CAR) and neutrophil‐to‐lymphocyte ratio (NLR) at the time of relapse. Additionally, we investigated biomarkers predictive of short‐term survival. Results: Among 231 patients, 91 patients experienced relapse and 74 patients died during the follow‐up period. Multivariate analysis revealed that treatment after relapse, CAR, and NLR was significantly associated with overall survival. Among them, treatment after relapse significantly affected survival outcomes, and patients who received definitive local treatment had a better 3‐year survival rate than those who received other treatments. Conversely, NLR was the most influential biomarker for short‐term survival, and the prognosis of patients with high NLRs was much worse than those with low NLRs. Conclusions: This study thus demonstrated that, for the patients with recurrent cervical cancer who received radiation‐based therapy, definitive local treatment can provide long‐term survival and extremely high NLRs are predictive of short‐term survival.